Insulin-like growth factor-II: new roles for an old actor - Cianfarani, Stefano (Frontiers in Endocrinology, 2012)
IGF-II, traditionally considered as a growth factor implicated in growth of fetal tissues and cancer cells, is now emerging as a potential metabolic regulator. The aim of this overview is to provide the available evidence, obtained in both experimental conditions and in humans, for a role of IGF-II in the fine-tuning of metabolism and body composition. The underlying mechanisms and the potential clinical implications are discussed.